EFEKTIVITAS ANTIBAKTERI MINYAK ATSIRI DAUN EUKALIPTUS (Eucalyptus globulus) DALAM SEDIAAN KRIM SEBAGAI ANTIBAKTERI Staphylococcus aureusATCC 29213 - Intan Martha Cahyani; Miftakhul Khoeriyah (Universitas Wahid Hasyim Semarang, 2017)
ABSTRACT Staphylococcus aureus is one of the acne-causing bacteria. 1,8 cineole is the content of eucalyptus leaves oil which has antibacterial activity Staphylococcus aureus. This research aimed to examine the effective consentration of eucalyptus leaves oil as an Staphylococcus aureus ATCC 29213 antibacterial. Eucalyptus leaves oil made in series a concentration of 5%, 7,5% and 10% for antibacterial activity test using the pitting diffusion method. Based on the test result of antibacterial activity gained an average diameter of inhibition zone eucalyptus leaves oil successively 1,286 cm; 1,424 cm; 1,574 cm. The statistically test results showed significant difference in the antibacterial activity of eucalyptus leaves oil in concentrations 5%, 7,5% and 10% to the growth of Staphylococcus aureus ATCC 29213. Eucalyptus leaves oil has an effective concentration of 10% as an antibacterial stapgylocuccus aureus and made cream formula. Test of antibacterial activity obtained resistibility zone diameter 1,136 cm. The result of t-test indicated that cream formula has significant effect on antibacterial activity. Keywords: Eucalyptus leaves oil, antibacterial effectivity, cream.